2021
DOI: 10.1177/20533691211028518
|View full text |Cite
|
Sign up to set email alerts
|

Safety of hormone replacement therapy in women with a history of cervical adenocarcinoma

Abstract: Objectives Studies investigating the safety of hormone replacement therapy in cervical cancer have predominantly included patients with squamous disease. Pathological studies have identified estrogen receptor positivity in cervical adenocarcinomas. A recent small case-control study suggested a trend towards reduced survival with hormone replacement therapy in cervical adenocarcinomas. Our objective was to determine if hormone replacement therapy use in patients treated for cervical adenocarcinomas is detriment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…A recent retrospective cohort study of 244 women who received vaginal estrogen found no increased risk of cervical cancer recurrence, and in this study, 40.3% of the cervical cancer cohort had prior adenocarcinoma 71 . Furthermore, in a very recent small retrospective study of women younger than 50 years with stage 1B–2B cervical adenocarcinomas, there was a trend toward improved survival rates with hormone replacement therapy 75 …”
Section: Part 1: Intravaginal Estrogensupporting
confidence: 59%
See 1 more Smart Citation
“…A recent retrospective cohort study of 244 women who received vaginal estrogen found no increased risk of cervical cancer recurrence, and in this study, 40.3% of the cervical cancer cohort had prior adenocarcinoma 71 . Furthermore, in a very recent small retrospective study of women younger than 50 years with stage 1B–2B cervical adenocarcinomas, there was a trend toward improved survival rates with hormone replacement therapy 75 …”
Section: Part 1: Intravaginal Estrogensupporting
confidence: 59%
“…71 Furthermore, in a very recent small retrospective study of women younger than 50 years with stage 1B-2B cervical adenocarcinomas, there was a trend toward improved survival rates with hormone replacement therapy. 75…”
Section: History Of Adenocarcinoma Of the Cervixmentioning
confidence: 99%
“…A recent retrospective review evaluating the safety of HRT specifically in AC patients was published in 2021 [ 60 ]. In this review, all women with stage 1B–2B AC under the age of 50 were enrolled.…”
Section: Resultsmentioning
confidence: 99%
“…Most cervical cancers are squamous cell carcinoma so they are non-estrogen dependent. 12 A systematic review conducted in 2021 of the PubMed English literature determined HRT had no detrimental effect on cervical cancer oncological outcomes, while several benefits were demonstrated, including reduced metabolic risk and improved quality of life, suggesting HRT should be offered to young cervical cancer survivors for early menopause management. 12 , 13 Providing clear guidance to GPs and GP champions in menopause for managing menopausal women with a personal history of gynaecological cancer through training and conferences would help reduce the delay in treating affected women.…”
Section: Discussionmentioning
confidence: 99%